Adoption of digital media by African language print newspapers: the case of Isolezwe - Salawu, Abiodun; Tsutsa, Fortune; Mpofu, Phillip (Penerbit Universiti Kebangsaan Malaysia, 2022)
Digital media have transformed media’s news gathering, production and news dissemination traditions. However, African language newspapers’ use of digital media has been overlooked and understudied. Therefore, this study explores the adoption of digital media by Isolezwe, a South African indigenous language newspaper that publishes in IsiZulu. Data were gathered using the interview and observation methods. Deploying strands drawn from media convergence and diffusion of innovation theories, the study shows the convergence of African language print media and digital media, and advancement of African language newspapers towards increasing their digital and social media presence. This development has positively enhanced Isolezwe’s journalistic functions of newsgathering and dissemination. The study provides insights into understanding African language journalism in the context of the advancement of digital and communication technologies. Findings from this research show that Isolezwe has expanded its digital presence to social media. Over and above the online version, Isolezwe is also actively engaged on Twitter and Facebook which are the two most popular social networking sites in South Africa. The platforms are strategically deployed for newsgathering and news dissemination purposes. This is a timely contribution to existing scholarship on the adoption of digital media by indigenous languages newspapers in South Africa in particular and Africa in general. The study also provides insights into understanding African language journalism in the context of the advancement of digital and communication technologies.